EFFECTS OF OZONE TREATMENT ON 0.05% CHLORHEXIDINE BIGLUCONATE SOLUTION: ASSESSMENT OF CRYSTALLOGRAPHY RESULTS IN AN IN VITRO EXPERIMENT - Kurylo, V.O.; Коrol, D.М.; Rozhko, M.М.; Kindii, D.D.; Toncheva, K.D.; Kozak, R.V. (Problemy ekolohiï ta medyt︠s︡yny, 2024)
This study explores the impact of ozone treatment on a 0.05% chlorhexidine gluconate solution, focusing on potential changes in molecular structure and corresponding crystallographic transformations at the regularity level following the completion of the wedge dehydration process. The aim of this study is to assess the effect of ozone treatment on a 0.05% chlorhexidine solution, especially focusing on determining the optimal time for ozonation process performance and the period of its effect duration based on the results of crystallography. The methodology employed involves an open-air thesis and subsequent microscopic examination of crystal formation results. The ImageJ software (Wayne Rasband, USA) was applied to study morphological changes in the crystal formation process through a structured algorithm of sequential actions. Micrograph analysis led to the identification of five characteristic crystal morphotypes, which can be categorized based on the increasing complexity of crystal element shapes. Result. The study explored the potential application of ozonated chlorhexidine in dental protocols. This paper presented a comprehensive analysis of the general crystallographic characteristics of chlorhexidine in a 0.05% solution, demonstrated changes in crystallograms found in samples of ozonated chlorhexidine, investigated the impact of ozone treatment time on crystal formation features, as well as explored the duration of the ozonation effect on 0.05% chlorhexidine gluconate solution based on crystallographic results. Conclusions. Ozone treatment of a 0.05% solution of chlorhexidine bigluconate changes the process of crystal formation towards its activation, promotes the clustering of small crystals, the formation of crystals of the second type and the development of complex structures. These morphological changes lead to a decrease in the fractal index of crystals. Changes in the fractal index remain noticeable for 7 days after ozone treatment, indicating that the activation of crystal formation is irreversible. This opens up the possibility of using a solution of ozonated chlorhexidine 0.05% in dental protocols.